The normative imputation in extra-contractual civil liability. - Trejos Teheran, Luis Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article deals with the different theories that have been created on causality applied in civil liability, hence the objective of this research is to develop normative imputation as a constitutive axis of civil liability, for which a test of normative applicability must be created, since -as has been observed in judicial praxis- the causal nexus lacks some kind of test that allows judges to effectively apply causality. Thus, through the construction of documentary analysis matrices and the use of emerging categories from grounded theory, it was obtained that the causalist theory has structural shortcomings and that it is necessary to propose a new structuring element that contains an applicability test that provides legal operators with the necessary tools to effectively attribute civil liability. The creation and development of a normative test of a scientific and legal nature strong enough to give the respective solidity to the new structuring element such as normative imputation was also obtained.